THE OBLIGATION OF NOTARY TO REPORT SUSPICIOUS FINANCIAL TRANSACTIONS BASED ON THE VALUE OF THE TRANSACTION - Fadila, Ilham Zain; Sugiri, Bambang; Wisnuwardhani, Diah Aju (Fakultas Syariah, 2020)
Government makes various efforts to prevent the crime of money laundering. One of them is to encourage some parties to participate in supervising the suspicious financial transaction. In its practice, this triggers juridical problem such as verification and monitoring policies of financial transaction on the service users by the notaries. This research aims to describe the notaryâ€™s criteria and legal responsibilities on the suspicious transaction. This article is based on the doctrinal legal research with statute and conceptual approaches. The research result shows that the criteria of suspicious financial transaction have been set in Indonesian legislation. The notary has legal responsibility to identify and verify the service users of authentic deed issue in implementing precautionary principles. This responsibility is accompanied by administrative sanction which is in line with the Regulation of the Minister of Law and Human Rights No. 9 of 2017, concerning the Implementation of Knowing Your Customer Principles for the Notary.Pemerintah melakukan berbagai upaya mencegah terjadinya tindak pidana pencucian uang. Salah satunya, mendorong berbagai pihak untuk turut serta mengawasi terjadinya traksaksi keuangan yang mencurigakan. Dalam pelaksanaannya, upaya ini menimbulkan problem yuridis. Seperti kebijakan verifikasi dan pemantauan transaksi keuangan pengguna jasa oleh notaris. Penelitian ini bertujuan untuk mendeskripsikan kriteria dan tanggung jawab hukum notaris terhadap terjadinya transaksi keuangan mencurigakan. Artikel ini berdasarkan penelitian hukum doktrinal, dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa kriteria transaksi keuangan menurigakan sudah diatur dalam peraturan perundang-undangan di Indonesia. Notaris memilikiÂ tanggung jawab hukum untuk mengidentifikasi dan memverifikasi pengguna jasa pembuatan akta autentik dalam rangka penerapan prinsip kehati-hatian. Tanggung jawab ini disertai sanksi administrasi sesuai Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor 9 tahun 2017 tentang Penerapan Prinsip Mengenali Pengguna Jasa Bagi Notaris.